2015
DOI: 10.1016/j.bpj.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Dynamic Control of Binding

Abstract: Proteins have a highly dynamic nature and there is a complex interrelation between their structural dynamics and binding behavior. By assuming various conformational ensembles, they perform both local and global fluctuations to interact with other proteins in a dynamic infrastructure adapted to functional motion. Here, we show that there is a significant association between allosteric mutations, which lead to high-binding-affinity changes, and the hinge positions of global modes, as revealed by a large-scale s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Such a property plays an important role in the functionality of the proteins. For example, for allosteric proteins, long-range correlations warrant the binding at one site can be transmitted to other functional sites [13,14], and enable the high susceptibility for proteins in cellular environments. Based on the correlation analysis of structural ensembles determined by solution nuclear magnetic resonance (NMR), it was already demonstrated that the native proteins exhibit long-range correlations and high susceptibility in the native dynamics [15].…”
Section: Introductionmentioning
confidence: 99%
“…Such a property plays an important role in the functionality of the proteins. For example, for allosteric proteins, long-range correlations warrant the binding at one site can be transmitted to other functional sites [13,14], and enable the high susceptibility for proteins in cellular environments. Based on the correlation analysis of structural ensembles determined by solution nuclear magnetic resonance (NMR), it was already demonstrated that the native proteins exhibit long-range correlations and high susceptibility in the native dynamics [15].…”
Section: Introductionmentioning
confidence: 99%
“…The first release has been used as a basis for many further studies, including the development of energy functions [48], [46] which were subsequently implemented in the CCharPPI web server for characterising protein-protein interactions [49], as well as being used for ranking docked poses [45], [58], [6], [50]. SKEMPI has also been used to study human disease [56], [16], [55], assessing the role of dynamics on binding [69], exploring the conservation of binding regions [28], evaluating experimental affinity measurement methods [22], as well serving as a data source for models which predict dissociation rate changes upon mutation [1], pathological mutations [23], hotspot residues (e.g. [30], [44], [42], [66]) and changes in binding energy (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, they can resemble bound states to a biological partner 610 , active states of enzymes 11–14 , or conformations that are stabilized by a post-translational modification (PTM) 6, 11 , as well as altered by a disease-related mutation 15 .…”
Section: Introductionmentioning
confidence: 99%